2021
DOI: 10.1186/s13287-021-02227-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibronectin, FGF-2, and BMP4 in the stemness maintenance of BMSCs and the metabolic and proteomic cues involved

Abstract: Background Growing evidence suggests that the pluripotent state of mesenchymal stem cells (MSCs) relies on specific local microenvironmental cues such as adhesion molecules and growth factors. Fibronectin (FN), fibroblast growth factor 2 (FGF2), and bone morphogenetic protein 4 (BMP4) are the key players in the regulation of stemness and lineage commitment of MSCs. Therefore, this study was designed to investigate the pluripotency and multilineage differentiation of bone marrow-derived MSCs (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…UC-MSCs secrete a range of growth factors, such as hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 (SDF-1), keratinocyte growth factor (KGF), fibroblast growth factor (FGF), and insulin-like growth factor-1 (IGF-1), to facilitate proliferation and tissue damage repair. 45 , 46 MSCs have the potential to be pluripotent and capable of giving rise to a variety of cell types. The properties of various factors, growth factors, and extracellular vesicles can be transmitted.…”
Section: Preclinical Experimentsmentioning
confidence: 99%
“…UC-MSCs secrete a range of growth factors, such as hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 (SDF-1), keratinocyte growth factor (KGF), fibroblast growth factor (FGF), and insulin-like growth factor-1 (IGF-1), to facilitate proliferation and tissue damage repair. 45 , 46 MSCs have the potential to be pluripotent and capable of giving rise to a variety of cell types. The properties of various factors, growth factors, and extracellular vesicles can be transmitted.…”
Section: Preclinical Experimentsmentioning
confidence: 99%
“…[31][32][33] Many studies have reported that MSCs could greatly regulate inflammation and improve MI cardiac angiogenesis, and these regeneration effects were greatly related to the stem cell properties. [34][35][36][37] In this study, after 5-day dynamic cultivation in vitro, MSCs maintained high expressions of typical stem cell markers CD29 and CD90 on the PCT/collagen scaffold. Moreover, in vitro results showed that the PCT/collagen scaffolds were beneficial for MSCs adhesion and proliferation, and they could provide physical protection for MSCs in infarct area.…”
Section: Discussionmentioning
confidence: 62%
“…BMP family genes may play a regulatory role in pluripotency and multiline differentiation of bone marrow-derived mesenchymal stem cells and can participate in dry maintenance metabolism and proteomics. 14 The expression of miRNAs related to the MAPK signaling pathway, PI3K-Akt signaling pathway, focal adhesion signaling pathway, Rap1 signaling pathway, metabolic pathways, and pathways related to cancer, apoptosis, and axon guidance increased during the development of E15.5 and E17.5 embryos of Bmp5 short ear mice. The growth factor signal mediated by receptor tyrosine kinases is important for the normal formation and development of the NC.…”
Section: Discussionmentioning
confidence: 99%
“…BMP family genes may play a regulatory role in pluripotency and multiline differentiation of bone marrow-derived mesenchymal stem cells and can participate in dry maintenance metabolism and proteomics. 14…”
Section: Discussionmentioning
confidence: 99%